Brain Drain and Brain Return: Theory and Application to Eastern-Western Europe - Karin Mayr; Giovanni Peri (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
Recent empirical evidence seems to show that temporary migration is a widespread phenomenon, espe- cially among highly skilled workers who return to their countries of origin when these begin to grow. This paper develops a simple, tractable overlapping generations model that provides a rationale for return migra- tion and predicts who will migrate and who returns among agents with heterogeneous abilities. The model also incorporates the interaction between the migration decision and schooling: the possibility of migrating, albeit temporarily, to a country with high returns to skills produces positive schooling incentive effects. We use parameter values from the literature and data on return migration to simulate the model for the Eastern-Western European case. We then quantify the effects that increased openness (to migrants) would have on human capital and wages in Eastern Europe. We find that, for plausible values of the parameters, the possibility of return migration combined with the education incentive channel reverses the brain drain into a significant brain gain for Eastern Europe.
Keywords: F22; J61; O15; 330; Skilled Migration; Return Migration; Returns to Education; Eastern-Western Europe